2005
DOI: 10.1016/j.jvs.2005.03.024
|View full text |Cite
|
Sign up to set email alerts
|

Smoking and the patency of lower extremity bypass grafts: A meta-analysis

Abstract: Continued smoking after lower limb bypass surgery results in a threefold increased risk of graft failure. Smoking cessation, even if instigated after the operation, restored graft patency towards the patency of never smokers. These results indicate that adequate smoking cessation strategies in patients eligible for lower limb bypass surgery are of utmost importance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
58
1
8

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 168 publications
(74 citation statements)
references
References 38 publications
3
58
1
8
Order By: Relevance
“…Smoking independently increases the risk of graft failure by ≤4-fold. 33 It was recently shown that smokers with atherosclerotic diseases benefit more from antiplatelet therapy targeting the P2Y 12 -receptor than nonsmoking atherosclerotic patients. However, the mechanism remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Smoking independently increases the risk of graft failure by ≤4-fold. 33 It was recently shown that smokers with atherosclerotic diseases benefit more from antiplatelet therapy targeting the P2Y 12 -receptor than nonsmoking atherosclerotic patients. However, the mechanism remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…The number of cigarettes smoked is associated with the severity of the disease and a higher risk of amputation. Moreover, in the case of vascular grafts there is a three-fold higher risk of therapy failure with continuation of smoking [10,18,19]. Several randomised studies clearly demonstrate the advantage of anti-smoking therapy with the use of substitutes for nicotine [9,10,20].…”
Section: Discussionmentioning
confidence: 99%
“…However, smoking cessation is associated with a reduced risk of cardiovascular events and a reduced risk of amputation. Those patients that do undergo bypass surgery have a three-fold increased risk of graft failure with continued smoking which reduces to that of non-smokers with smoking cessation (Willigendael et al, 2005). These significant findings make smoking cessation a pre-requisite for any semi-elective or elective bypass surgery.…”
Section: Smoking Cessationmentioning
confidence: 99%